Associations Between Polybrominated Diphenyl Ethers Concentrations in Human Placenta and Small for Gestational Age in Southwest China - Liu, Yi-jun; Xie, Yan; Tian, Ying-kuan; Liu, Hui; He, Cai-die; An, Song-lin; Chen, Wei; Zhou, Yuan-zhong; Zhong, Xiao-ni (Frontiers in Public Health, 2022)
Background Prenatal exposures to polybrominated diphenyl ethers (PBDEs) may affect fetal growth. Small for gestational age (SGA) is a measure based on birth weight and gestational age at birth and represents a good indicator of fetal growth but it has been used only in a small number of studies. The present study aimed to examine the associations between PBDEs exposure and the risk of SGA among participants from a birth cohort in Southwest China. Methods The concentrations of eight common PBDE congeners (BDE-28, BDE47, BDE-99, BDE-100, BDE-153, BDE-154, BDE-183, and BDE-209) in 996 human placental samples collected between May to October 2020 were determined. A questionnaire survey was administered regarding maternal characteristics. The outcome data of the newborns were obtained from the medical record. The Mann–Whitney U test and binomial logistic regression analysis were used to assess associations between PBDEs concentrations (as a continuous or categorical variable) and SGA. Results All PBDE congeners were detected in more than 73% of samples. The median concentrations of ΣPBDEs were 10.08 ng/g lipid weight (lw). BDE-209 was the most abundant PBDE congener, contributed 28% to ΣPBDEs. There were 114 (11.4%) SGA infants. The levels of BDE-99, BDE-100, BDE-209, and the total levels of ΣPBDEs in the SGA group were significantly higher than those in the controls. When classifying the PBDEs concentrations as two categories: low and high, high level of ΣPBDEs was associated with increased risk of SGA [odds ratio (OR): 2.203, 95% confidence interval (CI): 1.453–3.340] after adjusting for potential covariates. The association remained significant when stratifying the data by gender of the newborn (OR: 2.572, 95% CI: 1.337–4.947 for boys; OR: 2.385, 95% CI: 1.315–4.325 for girls). Conclusion The present study adds to the literature by using placenta to measure PBDEs exposure during pregnancy, and provides evidence that prenatal exposure to PBDEs may be associated with the risk of SGA, at least at the levels of exposure in our population.